2021
DOI: 10.1155/2021/6104529
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Antagonizes Glucose Fluctuation-Induced Renal Injury by Inhibiting Aerobic Glycolysis via the miR-489/LDHA Pathway

Abstract: It has been considered that glucose fluctuation (GF) plays a role in renal injury and is related to diabetic nephropathy (DN) development. But the mechanism is still unclear. Aerobic glycolysis has become a topical issue in DN in recent years. There is an internal connection between GF, aerobic glycolysis, and DN. Curcumin (Cur) is a principal curcuminoid of turmeric and possesses specific protective properties in kidney functions. Cur also participates in the regulation of aerobic glycolysis switch. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In diabetic mice and human patients, Sas et al demonstrated the upregulation of glycolytic enzymes accompanied by increased glucose metabolism in kidneys ( 50 ). More recently, aerobic glycolysis was implicated in kidney injury caused by glucose fluctuation ( 51 , 52 ). These studies suggest the involvement of aerobic glycolysis or the Warburg effect in the development of renal diseases.…”
Section: Regulation Of Glucose Metabolism In Kidney Diseasesmentioning
confidence: 99%
“…In diabetic mice and human patients, Sas et al demonstrated the upregulation of glycolytic enzymes accompanied by increased glucose metabolism in kidneys ( 50 ). More recently, aerobic glycolysis was implicated in kidney injury caused by glucose fluctuation ( 51 , 52 ). These studies suggest the involvement of aerobic glycolysis or the Warburg effect in the development of renal diseases.…”
Section: Regulation Of Glucose Metabolism In Kidney Diseasesmentioning
confidence: 99%
“… 34 The condition of DKD patients was improved when LDHA was used as a therapeutic target. 31 , 35 However, serum lactate levels in DKD patients are higher than those in healthy controls, which may be affected by the use of drugs, like ARB drugs. 31 This suggests the necessity for larger sample and multicenter studies to detect serum lactate levels, while also paying attention to the effects of drugs on lactate metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…One of the actions of miR-489 is to regulate apoptosis by targeting 3’-UTR of IGF-I, which inhibits its expression [ 54 ]. Also, glucose fluctuations reduce miR-489 expression [ 55 ]. In this way, this miRNA function appear to be related to glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%